Prevalence of sexual dysfunction in HTLV-1 patients without spastic paraparesis and the association with psychiatric symptoms - Maedeh Kamrani; Narges Niazi Rad; Fariba Zemorshidi; Majid Khadem-Rezaiyan (Indian Journal of Psychiatry)
Introduction: The findings of previous studies are inconclusive in terms of psychological abnormalities and sexual function in asymptomatic human lymphotropic virus type 1 (HTLV-1) carriers. Aim: This study aimed to evaluate the prevalence of sexual dysfunction and its relationship with psychological abnormalities in asymptomatic HTLV-1 carriers. Materials and Methods: This cross-sectional study was conducted on asymptomatic HTLV-1 patients who were referred to the Neurology Clinic of a tertiary hospital in Mashhad, Iran. Patients with spastic paraparesis, leukemia, and uveitis, and those with an expanded disability status scale (EDSS) score higher than 2 were excluded. Sexual function in male and female subjects was evaluated using the brief male sexual function inventory (BMSFI) and female sexual dysfunction index (FSFI) questionnaires, respectively. The severity of psychological symptoms was evaluated in all patients using the symptom checklist-90-revised (SCL-90-R) questionnaire. Results: A total of 117 patients (61 males and 56 females) with a mean age of 35.3 ± 6.3 years were evaluated. Overall, 50.9% of males had a high and 39.3% of females had a good sexual function. Both male and female patients with poor sexual function were older and had more children compared to those with good sexual function (P < 0.05). There was no significant difference in the distribution pattern of SCL-90 domains between patients with high and low to moderate sexual function among male patients (P > 0.05). Depression, hostility, interpersonal sensitivity, paranoid ideation, and psychological abnormality were significantly more prevalent in female patients with poor sexual function compared to those with good sexual function (P < 0.05). Conclusion: The prevalence of psychological abnormalities was high in female with sexual dysfunction and these disorders might have a negative effect on various dimensions of sexual function.